Regional Variations in Physical Fitness and Activity in Healthy and Overweight Ecuadorian Adolescents - Cheryl A. Howe; Sharon Casapulla; Jay H. Shubrook; Pablo Lopez; Mario Grijalva; Darlene E. Berryman (MDPI AG, 2018)
Background: Insufficient physical activity (PA) and excessive sedentary behavior (SB) are the main contributors to adolescent obesity. However, it is uncertain whether recent economic growth and urbanization in Ecuador are contributing to an obesogenic environment. This study assessed the relationships among fitness, PA, SB, and perceived social support for PA in adolescents from urban (Quito) and rural (Loja) Ecuador. Methods: Fitness was estimated using 3-min step test and PA and SB participation and social support for PA were self-reported in 407 adolescents. T-tests and analysis of variance assessed differences by sex, obesity status, and region of Ecuador. Pearson correlations assessed relationships among PA, SB, fitness, and social support. Results: Males and rural adolescents (48.3 ± 9.4 and 47.1 ± 9.6 mL/kg/min) were more fit than females and urban adolescents (41.1 ± 7.5 and 39.7 ± 6.1 mL/kg/min). Fitness was negatively correlated with obesity only in rural Ecuador. Few adolescents reported ≥60 min/day of PA (8.4%) or ≤2 h/day of SB (30.2%), with greater SB participation in rural Ecuador. Weak correlations were observed among fitness, PA, SB, and parental/peer support for PA (r = −0.18 to 0.19; p < 0.05). Conclusion: While fitness varied by sex, weight status, and region, SB participation and parent/peer support for PA, not PA participation itself, predicted fitness in rural Ecuadorean adolescents.